Abrasion Indicators for Smart Surfaces Based on a Luminescence Turn‐On Effect in Supraparticles - Wenderoth, Sarah; Granath, Tim; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Advanced Photonics Research, 2020)
Slight mechanical damage on surfaces or coatings caused, for example, by shear stress, is hardly detectable by simple means. Therefore, shear stress indicator particles for the creation of “interactive and communicating” coatings are presented. These are core-shell supraparticles obtained by a two-step spray-drying assembly process from nanoparticle dispersions. Three different types of nanoparticles are used to create the supraparticles: dye-doped silica nanoparticles responsible for the fluorescence signal, iron oxide nanoparticles acting as a fluorescence absorber, and pure silica nanoparticles regulating the indicator sensitivity. The creation of two different types of indicator systems is feasible by changing the nanoparticle arrangements within the supraparticle: A turn-off and a turn-on system, which indicate—after incorporation into a coating—shear stress by the decrease or the increase in the fluorescence intensity, respectively. Herein, two different mechanisms compete with each other: on the one hand, the change in the fluorescence signal due to physical light-absorbing effects, and on the other hand, the abrasion of luminescent material. The clear superiority of the turn-on system to achieve a reliable signal is demonstrated in this work. With the particle systems, interactive and communicating surface coatings are established.<br